Hubungan Antara Need To Belong Dengan Presentasi Diri Online Pada Remaja Pengguna Instagram di SMP Al Azhar Syifa Budi Solo - Laili Rohmatika; Hardjono .; Rahmah Saniatuzzulfa (UNS Press, 2023)
The purpose of this study was to examine the relationship between the need to belong and online self-presentation among teenage Instagram users at SMP Al Azhar Syifa Budi Solo. The need to belong refers to an individual's desire to be accepted in a group of friends and to interact with other friends. Online self-presentation is an individual's effort to project an image to others to fit the situation and be accepted by others by implementing strategies to achieve the desired and expected self-image online. This research used quantitative methods. The sampling technique used stratified cluster random sampling. The number of samples obtained was as many as 166 students of 13-16 years old . The instruments used in this scale were the online self-presentation scale (ri= 0.914) and the need to belong scale (ri= 0.881). The results of the analysis indicated that the need to belong had a significant positive relationship with online self-presentation among teenage Instagram users at SMP Al Azhar Syifa Budi Solo (p < 0.05; 0.02 < 0.05). Need to belong contributed 6% influence on online self-presentation (R2 = 0.06).The purpose of this study was to examine the relationship between the need to belong and online self-presentation among teenage Instagram users at SMP Al Azhar Syifa Budi Solo. The need to belong refers to an individual's desire to be accepted in a group of friends and to interact with other friends. Online self-presentation is an individual's effort to project an image to others to fit the situation and be accepted by others by implementing strategies to achieve the desired and expected self-image online. This research used quantitative methods. The sampling technique used stratified cluster random sampling. The number of samples obtained was as many as 166 students of 13-16 years old . The instruments used in this scale were the online self-presentation scale (ri= 0.914) and the need to belong scale (ri= 0.881). The results of the analysis indicated that the need to belong had a significant positive relationship with online self-presentation among teenage Instagram users at SMP Al Azhar Syifa Budi Solo (p < 0.05; 0.02 < 0.05). Need to belong contributed 6% influence on online self-presentation (R2 = 0.06).